Pemerataan Akses Pendidikan - Endry Setiawan; Ninik Handayani; Ranto Setiyono; Hermansyah Hermansyah; Ahmad Ahmad; Widyatmike Widyatmike (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Fair educational opportunities for all members of Indonesian society are the subject of this article. Improving educational equity requires a systemic approach, rather than focusing on a single area. All the way up to the calibre of the teachers, the state of the school system, and the curriculum in light of the changes brought about by the rise of industry 4.0. By taking a fair view of each region's circumstances, the government can work toward educational equality. In addition, local and state governments, as well as the federal government, must work together to achieve educational equality. Nowadays, in a democratic society, everyone has the right to an education. An adequate education is a fundamental human right, as stated in Article 146 of the Constitution of 1945 of the Republic of Indonesia.